Psychology and the teacher - Child, Dennis (Cassell, 1993)
This classic text, now in its fifth edition, provides a lucid and up-to-date introduction to psychology for teachers. Thoroughly revised, the text incorporates recent research and developments in psychology and education. It is accompanied by Dennis Child's Applications of Psychology for the Teacher, also published in the Cassell Education series.